2020
DOI: 10.1101/2020.08.29.20184366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential Community and Campus Covid-19 Outcomes Under University and College Reopening Scenarios

Abstract: Background: Significant uncertainty exists about the safety of, and best strategies for, reopening colleges and universities while the Covid-19 pandemic is not well-controlled. Little also is known about the effects that on-campus outbreaks may have on local non-student and/or higher-risk communities. Model-based analysis can help inform decision and policy making across a wide range of assumptions and uncertainties. Objective: To evaluate the potential range of campus and community Covid-19 exposures, infect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…A study looking at Fall 2020 classes has shown that counties with large universities with in-person instruction had a large increase in COVID-19 cases in the three weeks after school started, while counties with universities with remote instruction had a decrease in number of cases during this similar time frame [22]. While college students are typically at a low risk for severe infection and death, spread of COVID-19 on campuses has the potential to spill over into more vulnerable communities adjacent to campuses [23,24]. Additionally, long-term consequences of COVID-19 infections are not well understood [25], thus widespread infections amongst college students could plausibly lead to complications in the future.…”
Section: Background On Pandemicmentioning
confidence: 99%
“…A study looking at Fall 2020 classes has shown that counties with large universities with in-person instruction had a large increase in COVID-19 cases in the three weeks after school started, while counties with universities with remote instruction had a decrease in number of cases during this similar time frame [22]. While college students are typically at a low risk for severe infection and death, spread of COVID-19 on campuses has the potential to spill over into more vulnerable communities adjacent to campuses [23,24]. Additionally, long-term consequences of COVID-19 infections are not well understood [25], thus widespread infections amongst college students could plausibly lead to complications in the future.…”
Section: Background On Pandemicmentioning
confidence: 99%
“…Additionally, depending on campus priorities and resource limitations, different campuses can use this same data to model policies differently. The effectiveness of reopening policies is expected to be sensitive to a campus’ specific context that includes physical infrastructure, overarching guidelines, and human compliance [5]. For certain campuses policies might not need to be constrained by exposure risk as testing might be frequent, ubiquitous, and voluminous.…”
Section: Discussionmentioning
confidence: 99%
“…In the main paper, LC uses PageRank [42] as an illustrative algorithm to identify important location nodes. For robustness, we apply various additional algorithms to identify highly authoritative nodes in H — betweenness centrality [15], eigenvector centrality [5], and load centrality [29]. In the SI Appendix, we distinguish these different policies as LC PRank , LC BCen , LC ECen , LC LCen .…”
Section: Modeling Policies and Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…As of November 19, 2020, there have been over 321,000 cases at over 1,700 American colleges and universities (21). While college students are typically at a low risk for severe infection and death, spread of COVID-19 on campuses has the potential to spill over into more vulnerable communities adjacent to campuses (22,23). Additionally, long-term consequences of COVID-19 infections are not well understood (24), thus widespread infections amongst college students could plausibly lead to complications in the future.…”
Section: Introductionmentioning
confidence: 99%